Gill epithelium of an angler catfish, Chaca chaca (Siluriformes, Chacidae): Enzyme and glycoprotein histochemistry. (12th September 2019) - Mistri, Arup; Kumari, Usha; Mittal, Swati; Mittal, Ajay Kumar
Abstract: A series of histochemical techniques have been employed to localize alkaline phosphatase, acid phosphatase, non‐specific esterase, catalase and peroxidase; and to visualize and characterize glycoprotein (GPs) moieties in the epithelium of gill arch, gill filaments and secondary lamellae of an angler catfish Chaca chaca . The epithelium of gill arch and gill filament shows strong alkaline phosphatase activity in the deeper layer epithelial cells; strong non‐specific esterase activities in the outer layer epithelial cells; and weak acid phosphatase activity throughout the epithelium. The activity of these enzymes in the secondary lamellae is weak. The catalase and peroxidase show strong activities in the blood cells of the secondary lamellae. Various classes of GPs have been identified and characterized in the mucous secretions of the gill epithelium of C. chaca . These include—GPs with oxidizable vicinal diols, GPs with sialic acid residues without O‐acyl substitution and GPs with O‐sulphate esters. The functional significance of different enzymes in gill epithelium and the GPs in the mucus secreted on the surface has been discussed with the physiology of the gills in relation to the characteristic habit and habitat of the fish.